(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
In this age of artificial intelligence, the effective marketing of library services is essential for university libraries to remain relevant and attract patronage of undergraduate students, who are increasingly reliant on digital information sources. However, libraries may not experience effective patronage by students in this age of AI without innovative marketing techniques for users’ awareness. This study, therefore, investigated the influence of library marketing on library patronage among undergraduate students in private universities in Oyo State in this age of artificial intelligence. The study adopted a survey research design with a population of 11,790 undergraduates from four private universities in Oyo State. A multistage sampling technique was used to select 360 undergraduates for the study. A structured questionnaire was used for data collection, while descriptive and inferential statistics were used for data analysis. The findings revealed a high level of library patronage among undergraduate students in private universities, with different strategies to market their services to the user community. The result further showed that library marketing (ß=0.187, t=3.422, p<0.05) positively influence library patronage among undergraduate students in private universities in Oyo State. The study concluded that libraries should adopt innovative marketing more vigorously by leveraging on the AI tools to promote the services and activities of the library to the user community from time to time.